Sustainable Choices: Exploring Gen Z's Second-Hand Fashion Consumption and Perception in Bogotá and Cali (2024)
According to recent studies, Gen Z’s perception of second-hand fashion is changing how younger people approach buying clothes. Gen Z is aware of the environmental damage of climate change and is setting standards based on sustainability while navigating fashion as a way of self-expression and keeping up with the tendencies this world conveys. In Colombia, new thrift shops and customers have arisen to oppose fast fashion, its exponential contamination, and cruel practices. Colombian Gen Z second-hand fashion consumers have not yet been studied, so this article aims to help understand their tendencies and motivations regarding their approach to this market in the country. Through surveys and interviews, this study gathered answers from respondents in the cities of Bogotá and Cali, where important insights were analyzed based on their cultural differences.